Measuring physical function in children with airway support: a pilot study using computer adaptive testing. - Dumas HM; Rosen EL; Haley SM; Fragala-Pinkham MA; Ni P; O'Brien JE (Developmental Neurorehabilitation, 2010)
Objective: To assess the responsiveness, examine the scoring range and determine the efficiency of a multidimensional computer adaptive testing version of the Pediatric Evaluation of Disability Inventory (PEDI-MCAT) for children admitted to inpatient pulmonary rehabilitation. Methods: The PEDI-MCAT was completed by clinician report for 30 infants and children. Mean self-care and mobility admission scores were compared with discharge scores for the total group and two diagnostic sub-groups (prematurity and congenital/neurological conditions). The scoring range of the mobility and self-care scales was examined to determine placement of the scores along the overall PEDI-MCAT scale. Efficiency was determined using an internal clock and average number of items required for score generation. Results: Mean changes for the total group and both sub-groups were significant for both self-care and mobility, except for the prematurity group's mobility scores. Effect sizes were small-to-moderate. Scores for both groups were at the low end of the scoring ranges. Average time to complete the PEDI-MCAT was 1.57 minutes. Average number of items administered was nine for self-care and 11 for mobility. Conclusion: The PEDI-MCAT was responsive to change in physical function, although only low-ability items were needed. The PEDI-MCAT can potentially minimize clinician burden in inpatient settings.